2012
DOI: 10.5815/ijisa.2012.05.08
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Multiple Hand Gesture Recognition System for Human Computer Interaction

Abstract: Abstract-With the increasing use of computing devices in day to day life, the need of user friendly interfaces has lead towards the evolution of different types of interfaces for human co mputer interaction. Real t ime vision based hand gesture recognition affords users the ability to interact with computers in more natural and intuitive ways. Direct use of hands as an input device is an attractive method which can co mmunicate much more information by itself in comparison to mice, joysticks etc allowing a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…From that time on, topics of researches relates to ubiquitous computing expands into wide fields, such as distributed computing [5,23,32,38], mobile computing [7,19,33], location computing [8,24,26,43], mobile networking [17], context-aware computing [11,12,20,37], sensor networks [1,3,9, 25,27,29], human-computer interaction [35], artificial intelligence [14,15,15], machine learning [10,40], psychology, sociology, manufacturing and materials.…”
Section: Introductionmentioning
confidence: 99%
“…From that time on, topics of researches relates to ubiquitous computing expands into wide fields, such as distributed computing [5,23,32,38], mobile computing [7,19,33], location computing [8,24,26,43], mobile networking [17], context-aware computing [11,12,20,37], sensor networks [1,3,9, 25,27,29], human-computer interaction [35], artificial intelligence [14,15,15], machine learning [10,40], psychology, sociology, manufacturing and materials.…”
Section: Introductionmentioning
confidence: 99%
“…A "gesture" is defined as "a movement usually of the body or limbs that expresses or emphasizes an idea, sentiment, or attitude" (Merriam Webster 2019, page 525). Gestures are widely used as a natural form of communication between persons for simple actions such as pointing to objects to expressing feelings (Rautaray & Agrawal, 2012). Within the teacher-student learning process, instructors use hand and body gestures to convey topics, as well as use movement to keep students engaged during the lecture.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies reported that people's most commonly used gestures include hand and arm movement, adjustments to seating or posture, touching of one-self i.e. stroking hair, done primarily for self-soothing, and other typical nervous ticks or repetitive, involuntary movements (Rautaray & Agrawal, 2012;Sariyanidi, Gunes, & Cavallaro, 2014). In the current study, the observers focused on and recorded movements of the arm and hand to measure students' classroom engagement.…”
Section: Introductionmentioning
confidence: 99%
“…However, in many situations, such operations and interactions are impossible; in such a case, a user's natural body motion can be used as very useful information for the human-machine interaction. Therefore, considerable research efforts have been carried out on the techniques known as the natural user interface (NUI), in which the system attempts to track and recognize a user's action and this then provides a very efficient method for the interaction [1][2][3][4][5][6][7]. In particular, the NUI technique, which uses a user's bare hand information, is known as one of the most efficient methods that enables users to interact with any device.…”
Section: Introductionmentioning
confidence: 99%